Nitrogen fertigation affects crop yield, nitrogen loss and gaseous emissions: a meta-analysis - Zhu, Yuanpeng; Zhang, Houping; Li, Rongcheng; Zhu, Wendong; Kang, Yaohu (Nutrient cycling in agroecosystems, 2023)
The effects of nitrogen fertigation (NF) on crop yield, nutrient loss, and gaseous emissions are still a subject of controversy when considering real field conditions. In order to address these concerns, we performed a meta-analysis using data from 2546 paired-treatment data points taken from 139 field research publications, which compared crop yield and nitrogen (N) loss (plus gaseous emissions) in NF. In general, the findings suggest that NF has a substantial positive impact on enhancing crop yield and increasing nutrient loss and gaseous emissions ( P < 0.05). However, the impact of NF differed depending on various factors such as irrigation methods, environmental conditions, and fertilizer management practices. Consistent with this, the most significant effects in terms of crop yield, N loss, and gaseous emissions were observed when N was managed through fertigation using microirrigation or sprinkler irrigation. The outcomes of our study demonstrated that the implementation of NF in sub-arid areas led to the most remarkable improvements in crop yield and reduction in N loss and gaseous emissions ( P < 0.05). Additionally, our findings suggest that irrigated land with moderate N application (150 ~ 300 kg ha −1 ) serves as a more advantageous foundation for crop growth when employing NF. Under NF treatments, the crop yield for other types of crops was considerably higher compared to that of vegetables ( P < 0.05). Out of all fertilization methods, the application of both organic and chemical fertilizers together had the most significant effect on crop yield and nutrient retention. The magnitude of the impact of NF on crop yield showed significant correlations with the proportion of total N loss and ammonium N (NH 4 + ) loss. In conclusion, based on our findings, NF could be a viable method to enhance both crop yield and nutrient retention. This study provides the guide for farmers and agricultural managers to achieve high agronomic outcomes with a sustainable way.